Pendekatan Konseling Behavior Dalam Penanganan Remaja Bermasalah dan Perilaku Self Harm - Ana, Indah Fitri; Asrini, Yenti; Salsabila, Fara Naia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Teenagers with various problems and problems in their lives need guidance in living their lives and need help when facing problems. Problems that occur in teenagers' lives include problems in the family, school, relationships and in the use of social media. A counselor needs to provide guidance to teenagers who have problems. The research method used is the library research method. The data collection method used is the documentation method. The data sources used are books, journals and internet sites. The data collection technique and instrument is documentation. The data analysis technique used is the content analysis method. To maintain the accuracy of the study and prevent errors in information in data analysis, cross-library checks and re-reading of the literature were carried out. The results of this research are each research item with specific conclusions related to Behavioral Counseling in handling problematic adolescents. The results of the discussion of each item are as follows: Successful application of behavioral counseling in handling problematic adolescents. procedures for implementing behavioral counseling in handling problematic adolescents. Methods or techniques used by behavioral counseling in treating teenagers. Scope and objectives of implementing behavioral counseling.